Improving Fatigue Resistance of Spinning Machine Springs and Simulation of Fatigue - سعيد علي; سليمان علي; علي هترة (Latakia University Journal -Engineering Sciences Series, 2023)
The effect of heat treatment on the tensile strength and fatigue strength of carbon spring steel was studied. The main objective of this study was to improve fatigue resistance of springs by changing the microstructure using different types of heat treatments. Tensile and fatigue tests were used for evaluating the results of the experimental heat treatments. The tensile tests gave the maximum tensile strength of the material and the fatigue tests gave the number of cycles the material can withstand before failure occurs at certain stress level. Finally a 3D Model of a real life spring was done and fatigue simulation was conducted while taking into consideration the properties of the material that were acquired after the tensile and fatigue tests. The results showed improvements of fatigue resistance of springs using heat treatment.